Design, fabrication and testing a semi-automatic sewing device for personalized stent graft manufacturing - Hu,Y; Zhang,L; senici,C; Li,W; Abdelaziz,M; Yang,G-Z (IEEE/ASME Transactions on Mechatronics, 2019)
For the treatment of Abdominal Aortic Aneurysm (AAA), a personalised stent graft is used to ensure it fits tightly to the patients vessel geometry. A personalised stent graft is usually handmade which requires thousands of stitches and can take weeks or even months to complete. This delay may expose the patient to the risk of aneurysm rupture. This paper presents a robotic sewing device that can enhance the stent graft sewing speed by providing automated needle manipulation. It simplifies the sewing process and has the potential to achieve fully automated stent graft manufacturing via a vision-guided system. The device features a sewing probe that can switch a double pointed semi-circular needle between two movable jaws. This forgoes the need for manual needle handling including grasping, driving rotation, releasing and re-grasping, which requires a high level of manual dexterity and attention. This paper presents the design of the device, its mechanical synthesis and experimental validation. The focus of the paper is on the linkage parameter optimisation and needle locking mechanism design. The proposed device has been fabricated using 3D rapid prototyping techniques, and its performance has been compared with the conventional manual sewing method. The experimental results show that the device can achieve a 30% reduction of the completion time for a stitching task while achieving better consistency and quality of the stitches.